The presence of ACE2 and regulatory miRNAs (miR-200c-3p and miR-421-5p) in the saliva of periodontitis patients post-COVID-19 vaccination - Bachtiar, Boy M.; Haerani, Natalina; Soeroso, Yuniarti; Ismah, Nada; Bachtiar, Endang W. (Frontiers in Dental Medicine, 2024)
The effectiveness of mRNA vaccines for COVID-19 in individuals with periodontitis is crucial. This study evaluated the efficacy of the BNT162b2 vaccine in individuals with periodontitis who had been vaccinated at least six months. By using rt-PCR, the association between the SARS-CoV-2 receptor (ACE2) and miRNA-200c-3p and miRNA-421-5p as well as interleukin-6 (IL-6) was examined in the saliva of moderate (G1, n =10) and severe (G2, n =10) periodontitis subjects. Participants without periodontitis were included as control group. The transcription levels of sACE2 and Il-6 was higher in periodontitis participants than control, but within periodontitis groups, only Il-6 expression was observed higher in G2 compared to G1. A positive strong correlation between ACE2 and Il-6 was only observed in G2 group (p = 0.008). The expression of miR-200c-3p but not miR-421-5p was higher in periodontitis individuals. Their relationship was positive but a strong correlation was only noticed in G2 group. In all periodontitis groups, a strong inverse correlation was observed between the two micro RNAs (miRNAs) and ACE2. However, Receiver Operating Characteristic (ROC) analysis showed, only the relationship between ACE2 and miR-4215p reveals the probability as biomarker for the efficacy of the mRNA vaccine, with AUC (areas under the ROC curve) of 0.92 and 0.80 in G1 and G2, respectively. Our study revealed the efficacy of BNT162b2 is not interfered by active and nonactive periodontitis conditions at least six months post vaccination. This suggests, that in individual with periodontitis, the salivary soluble ACE2 may serve as indicator of vaccine response.